Pengembangan Tata Kelola Objek Wisata Makam Sunan Pandanaran Berbasis Teknologi Informasi Untuk Penguatan Kawasan Wisata Budaya - Minardi Minardi; Agung Prayogo; Hery Purnomo; Nurhadi Nurhadi (GUYUB: Journal of Community Engagement, 2026)
The religious tourism area of the Sunan Pandanaran Tomb in Paseban Village, Klaten, represents a significant cultural and local economic asset, with an average of approximately 10,000 pilgrims visiting each month based on management data. However, the operation of the Klaten–Semarang Toll Road has led to a decrease in the duration of visits and tourism-related economic activities. The main issue lies in the low level of digitalization in tourism information services, resulting in limited promotional reach, suboptimal visitor experiences, and underutilized economic benefits for the local community. This community service program employs a Participatory Action Research (PAR) approach, actively involving stakeholders through stages of problem identification, planning, implementation, and evaluation. The interventions include the development of a website-based information system, digital marketing training, and capacity building for tourism management human resources.Impact measurement was conducted using a pre-test and post-test design, with instruments consisting of structured questionnaires, participatory observation, and program performance indicators. Data analysis was carried out using descriptive quantitative methods to assess changes in participants’ knowledge and skills. The results indicate a significant improvement in information technology literacy, increasing from 60% to 95%, as well as an enhancement in operational digital system skills from 20% to 90%. Furthermore, user response evaluations show improvements in the quality of information services, the effectiveness of digital promotion, and the strengthening of destination branding. This program has contributed to improving the quality of tourism services, expanding promotional reach, and strengthening creative economic opportunities for the local community. It also supports the achievement of the Sustainable Development Goals (SDGs), particularly Goal 8 (Decent Work and Economic Growth) and Goal 11 (Sustainable Cities and Communities), through the development of inclusive and sustainable digital-based tourism.